HAMBATAN KOMUNIKASI DAN STRES ORANGTUA SISWA TUNARUNGU SEKOLAH DASAR - Damayanti, Indah; Purnamasari, Sri Hadiati (Program Studi Psikologi Universitas Pendidikan Indonesia, 2019)
Constraints in communication are generally experienced by parents with deaf children in elementary school age. The inability of children to hear and the lack of vocabulary of the children causes difficulties in understanding and conveying messages between parents and children. This causes the need for parents to convey and receive messages from children not achieved perfectly and cause stress. This study aimed to determine the relationship between barriers to communication with stress in parents with deaf children at primary school SLBN Pembina Pekanbaru. This study used correlational method. This research had 42 participants and used the instruments scale of communication barriers scale (Fajar, 2009) and stress scale based on Sarafino’s (1997) theories of stress and symptoms. The results showed the positive correlation of 0.819 (p smaller than 0.01).